The Failure Of The Political Struggle For Recognition Of Indonesian Muslim Blind People In Serang District - Silvia Dwi Adinda; Firyal Fazriani; Bunga Cahya Faqih; Galih Pramudya; Mahpudin Mahpudin (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Abstract Problem: The Indonesian Muslim Blind Association (ITNMI) is a community organization that brings together members of the visually impaired or blind Muslims in Serang district. This organization has been established since 2021 and is experiencing challenges due to the lack of recognition and support they should receive. They are labeled as a group that cannot live independently and is unproductive. On this basis, they struggle to be recognized by the state and society that they have the same abilities as other normal humans. Purpose: This article attempts to explain the forms and factors behind ITMI Serang Regency's failure to recognize ITMI in fighting for its recognition rights from the government and the social environment. Methodology: This research uses a qualitative case study method with interview, observation, and documentation data collection techniques. Results/ Findings: The research results show that the recognition struggle carried out by the Serang Regency ITMI Organization experienced failure or misrecognition. The factors that cause this to happen are internal, external, and economic factors. And there is mobilization based on personal interests which destroys the integral dignity of humanity and makes ITMI Serang Regency inactive again (mis-existence). Keywords: Recognition; Disability; Minority Struggle.